The right to health and vulnerable groups: a review of the recent jurisprudence of the Constitutional Tribunal - Hidalgo Talledo, Marco Antonio (2023)
Health is a right that has a constitutional scope and its configuration as a social right implies that the State has the responsibility to preserve and restore people's health, with the full support of society to promote and guarantee an increasingly solid quality of life. In this perspective, the right to health is closely related to the State's responsibility to carry out preventive measures to avoid harm to the health of people in vulnerable situations. The objective of this research is to analyze and understand the health status of vulnerable groups that require special attention, such as people with HIV-AIDS, children, adolescents, people living in poverty, people with disabilities and the elderly. It also aims to review the recent jurisprudence of our Constitutional Court, in order to describe the scope of this body to propose effective solutions that generate positive impact in the medium and long term. It is important to highlight that the right to health continues to evolve and progress, which implies that with the passing of time it is becoming increasingly linked to other fundamental rights.